2006
DOI: 10.1007/s10531-004-1236-4
|View full text |Cite
|
Sign up to set email alerts
|

Avian species richness and numbers in the built environment: can new housing developments be good for birds?

Abstract: Bird species richness (S) and numbers (N) were studied in the breeding season in housing developments of different ages in a small English town and compared with village sites, urban green corridors and adjacent arable farmland. S and N were highest in village and green corridor sites. S in urban plots ranged from 13 to 18 species, similar to farmland, but N was much lower in farmland. Marked differences in the number of individual species between plots were recorded. S and N were independent of age of develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…For example, Baldock et al [53] reported that bee species richness, important for pollinator services, was higher in urban areas than farmland [53]. In another study, Mason [54] reported that whilst bird species richness was similar between housing developments in a small town and adjacent arable farmland, bird numbers were much lower in the farmland. Green spaces in cities are usually split up into small patches surrounded by built-up areas.…”
Section: Biodiversitymentioning
confidence: 99%
“…For example, Baldock et al [53] reported that bee species richness, important for pollinator services, was higher in urban areas than farmland [53]. In another study, Mason [54] reported that whilst bird species richness was similar between housing developments in a small town and adjacent arable farmland, bird numbers were much lower in the farmland. Green spaces in cities are usually split up into small patches surrounded by built-up areas.…”
Section: Biodiversitymentioning
confidence: 99%
“…The availability of suitable nesting sites limits breeding density (Newton 1998) and with the removal of mature and dead trees typical of suburbia, there will be fewer natural nest sites in such areas (Wiebe 2011). Buildings may provide some cavities, but modern or refurbished houses tend to have fewer potential nesting holes to compensate for this loss of nesting sites (Mason 2006;Shaw et al 2008). As a result, the provision of nest boxes in urban areas may be a particularly valuable resource, allowing cavity nesters to prosper (Chace and Walsh 2006;Wiebe 2011) and providing an opportunity to investigate factors affecting urban bird breeding biology.…”
Section: Introductionmentioning
confidence: 99%
“…However, species diversity tends to decrease in comparison to other habitat types (Beissinger and Osbourne 1982;Blair 1996;Marzluff et al 2001). The House Sparrow (Passer domesticus, Linnaeus) is traditionally associated with human habitation, and is one of the few species that generally persists as urbanisation increases.…”
Section: Introductionmentioning
confidence: 99%